2023
DOI: 10.1093/femsml/uqad038
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of novel non-aggregative variants under negative frequency-dependent selection in Klebsiella variicola

Amandine Nucci,
Juliette Janaszkiewicz,
Eduardo P C Rocha
et al.

Abstract: Klebsiella variicola is an emergent human pathogen causing diverse infections, some of which in the urinary tract. However, little is known about the evolution and maintenance of genetic diversity in this species, the molecular mechanisms and their population dynamics. Here, we characterized the emergence of a novel rdar-like (rough and dry) morphotype which is contingent both on the genetic background and the environment. We show that mutations in either the nitrogen assimilation control gene (nac) or the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
3
4
0
Order By: Relevance
“…This nding is important when considering the population dynamics suggesting that when removed from an environment where mucoviscosity or antibiotic resistance is not necessary, they may be outcompeted and less prone to spread a worrisome trait. When considering the mbriae allele variants we found that, in line with recent work 30,36 , insertion sequences in mrkH led to decreased bio lm formation, as all three isolates with this insertion displayed limited bio lm formation (Fig. 5).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This nding is important when considering the population dynamics suggesting that when removed from an environment where mucoviscosity or antibiotic resistance is not necessary, they may be outcompeted and less prone to spread a worrisome trait. When considering the mbriae allele variants we found that, in line with recent work 30,36 , insertion sequences in mrkH led to decreased bio lm formation, as all three isolates with this insertion displayed limited bio lm formation (Fig. 5).…”
Section: Discussionsupporting
confidence: 87%
“…2). However, similar to what was recently shown with Klebsiella variicola 30 , within the entire collection, the operon csgABCDEF was not present suggesting the phenotypes observed on congo red is due to another factor. In complementation of the congo red analysis, when grown on calco uor white agar and visualized under UV uorescence we saw diverse uorescence, indicating variability in cellulose production within the entire collection (Supplemental Figure S2).…”
Section: Tablesupporting
confidence: 84%
See 3 more Smart Citations